Analysis of Financial Accounting Standards for Entities Without Public Accountability Application for Financial Statements at MSME Rahmah Laundry - Zulfitri, Sakinah; Syafina, Laylan; Nasution, Yenni Samri Julianti (Yayasan Sinergi Kawula Muda, 2024)
This research aims to analyze the application of the Finanscial Accounting Standard of Non-Public Accountability Entities ( SAK ETAP) as the basis in the preparation of financial report at Micro small and Medium Enterprises Rahmah Laundry. The research use a qualitative approach with descriptive analysis methods, Research data collection was carried out through observation, interviews, documentation, and other supporting sources obtained from the research location. This study highlight how Rahmah Laundry compiles there financial statement. The result of the research show the owner has not followed the standards set by Finanscial Accounting Standard of Non-Public Accountability Entities (SAK ETAP) in the recording and compilation of his financial report due to obstacles he faces such as low awareness, skills and knowledge of the owner of Rahmah Laundry about Finanscial Accounting Standard of Non-Public Accountability Entities (SAK ETAP).